Study of an Atmospheric Refractivity Estimation Using AREPS and Genetic Algorithm - Jang, Doyoung; Kim, Jongmann; Park, Yong Bae; Choo, Hosung (RFIT 2022 - 2022 IEEE International Symposium on Radio-Frequency Integration Technology, 2022)
In this paper, we propose an estimation method of an atmospheric refractivity according to altitude. To estimate the atmospheric refractivity, an artificial trilinear model that can express the ducting conditions is applied to a genetic algorithm (GA) process. The calculated clutter power spectrum using the designed trilinear model is then compared with the calculated clutter power spectrum based on the measured atmospheric refractivity data. The result demonstrates that the atmospheric refractivity can be predicted using the proposed method from the sea clutter powers.
Keywords: Atmospheric refractivity; Condition; Ducting; Estimation methods; Power; Power-spectra; Sea clutters; Trilinear model; estimation methods; genetic algorithm; wave propagation